EDITORIAL INTRODUCTION Sustainable Development Goals 2030: Challenges and Its Solutions - Diana Zuhroh; Dina Poerwoningsih; Pindo Tutuko; Sari Yuniarti (International Conferences SDGs 2030 Challenges and Solutions, 2030)
According to United Nations Development Programme, the SustainableDevelopment Goals (SDGs), otherwise known as the Global Goals, are auniversal call to action to end poverty, protect the planet and ensure that allpeople enjoy peace and prosperity. The goals listed in Sustainable DevelopmentGoals 2030 (SDGs) are an action plan for people, the planet and prosperity. It alsoseeks to strengthen universal peace in greater freedom. We are all aware thateradicating poverty in all its forms and dimensions, including extreme poverty,is the greatest global challenge and the indispensable requirement for sustainabledevelopment (Transforming our world: the 2030 Agenda for SustainableDevelopment). Under the agenda, all countries and all stakeholders, acting incollaborative partnerships, will implement the plan. On the agenda it wasdecided to free humanity from the tyranny of poverty and desire and to heal andsecure our planet. Furthermore, 17 Goals of SDGs seek to build the MillenniumDevelopment Goals and resolve what is not achieved, which is to achieve allhuman rights and to achieve gender equality and empowerment of all womenand girls. It should be integrated and inseparable and balancing the threedimensions of sustainable development: economic, social and environmental.